2011
DOI: 10.1210/jc.2010-2986
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Levothyroxine and Selenomethionine on Lymphocyte and Monocyte Cytokine Release in Women with Hashimoto's Thyroiditis

Abstract: Despite affecting different types of inflammatory cells, levothyroxine and selenomethionine exhibit a similar systemic antiinflammatory effect in euthyroid females with Hashimoto's thyroiditis. This action, which correlates with a reduction in thyroid peroxidase antibody titers, may be associated with clinical benefits in the prevention and management of Hashimoto's thyroiditis, particularly in subjects receiving both agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(149 citation statements)
references
References 35 publications
6
132
5
6
Order By: Relevance
“…Some authors defined subclinical hypothyroidism when concentrations of TSH are higher than 3.6 uIU/mL [15], others when it was higher than 4.0 uIU/mL [16] or 4.5 uIU/mL [17], and still others when it was higher than 5.7 uIU/mL [18]. It has recently been discussed whether the upper TSH range should be set around 2.5 mIU/L [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors defined subclinical hypothyroidism when concentrations of TSH are higher than 3.6 uIU/mL [15], others when it was higher than 4.0 uIU/mL [16] or 4.5 uIU/mL [17], and still others when it was higher than 5.7 uIU/mL [18]. It has recently been discussed whether the upper TSH range should be set around 2.5 mIU/L [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that a 6-month levothyroxine treatment reduces systemic inflammation in patients with Hashimoto's thyroiditis. This anti-inflammatory effect was described to be clinically relevant and to delay the progression of Hashimoto's thyroiditis even in euthyroid women [10]. A long-term follow-up of TPO-Abs in patients with Hashimoto's thyroiditis treated with levothyroxine demonstrated a 70% decrease in TPO-Abs after 5 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%